Gastric varices in patients with liver cirrhosis: pathogenesis, classification, and therapeutic management - Simon, Krzysztof; Stryczek-Lis, Marlena; Stępień, Kamil (Clinical and Experimental Hepatology, 2026)
This review paper discusses the pathogenesis, classification, and principles of prevention and treatment of portal hypertension, with particular emphasis on gastric varices. Gastric varices are less common than esophageal varices, but have distinct pathophysiology, classification, and management strategies, which justifies presenting them separately from other varices. The topics covered are based on the Baveno VII consensus, recommendations and findings from studies conducted in other countries, as well as on the authors’ own clinical experience. This paper is an expanded and updated version of the article published in Hepatologia (2025; 25: 96-101).